Against Permitted Exploitation in Developing World Research Agreements. Issue 1 (17th February 2015) - Wenner, Danielle M.
Abstract: This paper examines the moral force of exploitation in developing world research agreements. Taking for granted that some clinical research which is conducted in the developing world but funded by developed world sponsors is exploitative, it asks whether a third party would be morally justified in enforcing limits on research agreements in order to ensure more fair and less exploitative outcomes. This question is particularly relevant when such exploitative transactions are entered into voluntarily by all relevant parties, and both research sponsors and host communities benefit from the resulting agreements. I show that defenders of the claim that exploitation ought to be permitted rely on a mischaracterization of certain forms of interference as unjustly paternalistic and two dubious empirical assumptions about the results of regulation. The view I put forward is that by evaluating a system of constraints on international research agreements, rather than individual transaction‐level interference, we can better assess the alternatives to permitting exploitative research agreements.